Transformation of Upgrading MSMEs to Implementation Studies - Himlina, Himlina; Asmorowati, Sulikah; Setijaningrum, Erna (Publik : (Jurnal Ilmu Administrasi), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in economic growth, job creation, and innovation, both in Indonesia and in other countries such as India. Although MSMEs make a significant contribution to industrial output and employment, this sector still faces challenges such as limited financing, technology adoption, and market access. The government is trying to overcome these obstacles through funding, incentives, and regulatory simplification. Indonesia is recorded as the country with the largest number of MSMEs in ASEAN, with significant contributions to GDP and national workforce absorption. This study highlights efforts to strengthen MSMEs in Banyuwangi Regency through the "MSME Naik Kelas" program. With an economic structure that is still dominated by micro businesses, Banyuwangi focuses on strengthening access to capital, training, digitalization, and market expansion. This study uses a qualitative approach with literature study and case study methods. The policy implementation approach refers to the Edward III model which includes transmission, clarity, and consistency. The Banyuwangi government implements programs such as "Warung Naik Kelas (WeNak)" and "Jagoan Banyuwangi" to accelerate the development of MSMEs. The findings show that the effectiveness of communication, clarity of instructions, and consistency of implementation greatly determine the success of MSME transformation. In addition, support from regional regulations and a continuous monitoring system strengthen the effectiveness of the program. In conclusion, the success of MSME development in Banyuwangi does not only depend on the right policies, but also on adaptive communication strategies and the active involvement of business actors. This comprehensive support allows MSMEs to increase their competitiveness and contribute more to the regional economy